Implementation of Adaptive Centralized Protection Scheme in Active Networks with a HIL Setup - Pashaei, Meysam; Kauhaniemi, Kimmo; Laaksonen, Hannu (IEEE, 2024)
Power system protection is crucial for immediately isolating faulty regions to safeguard equipment, ensure uninterrupted service, and prioritize personnel safety. However, several challenges have prevented the adaptive, reliable, and secure operation of power system protection schemes in the past. The arrival of affordable and high-speed servers, improved communication links, and the maturation of standards such as IEC 61850 have paved the way for more effective power system protection. As a result, centralized adaptive protection, although not a novel concept, can now play a key role in the future active distribution networks that will operate closer to their voltage and thermal limits. These complex grids with a significant percentage of renewable energy sources require adaptive protection, continuous condition monitoring, and even new functionalities. This paper provides a comprehensive guide on how to establish an IEC 61850-based centralized adaptive protection scheme to increase dependability and security of power system. Finally, several case studies have been conducted using hardware-in-the-loop setup to discuss the challenges and opportunities in the implementation of the proposed schemes.
Keywords: Adaptive protection; centralized protection; directional overcurrent relay; differential relay; hardware-in-the-loop; IEC 61850; fi=Sähkötekniikka|en=Electrical Engineering|